2009
DOI: 10.1002/lary.20201
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography–computed tomography surveillance for the node‐positive neck after chemoradiotherapy

Abstract: Planned neck dissection can be deferred with a negative post-treatment PET-CT. Assuming a complete response at the primary site and a negative PET-CT scan, there may be a role for serial PET-CT surveillance in patients with residual palpable cervical lymphadenopathy. Laryngoscope, 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Similar data (Table 2) has been published by using PET-CT for excluding residual locoregional disease after definitive chemoradiotherapy for HNSCC [4045]. Ong et al showed that the sensitivity and specificity are higher if the PET-CT study is performed after 12 weeks or more from the end of chemoradiotherapy.…”
Section: Pet For Neck Evaluation After Definitive Chemoradiotherapy Fsupporting
confidence: 77%
“…Similar data (Table 2) has been published by using PET-CT for excluding residual locoregional disease after definitive chemoradiotherapy for HNSCC [4045]. Ong et al showed that the sensitivity and specificity are higher if the PET-CT study is performed after 12 weeks or more from the end of chemoradiotherapy.…”
Section: Pet For Neck Evaluation After Definitive Chemoradiotherapy Fsupporting
confidence: 77%
“…PET-CT scans were obtained in standard protocol as previously described in a prior study from our institution [14]. …”
Section: Methodsmentioning
confidence: 99%
“…26 There is a great deal of interest and excitement regarding the use of PET/CT as a modality for observing posttreatment response in the neck, and evidence suggests that PET/CT imaging has a greater than 94% NPV in nodal response. 9,11,27,28 A retrospective review of 65 patients with head and neck SCC by Ong et al 29 found PET/CT with an NPV of 97% in the neck. Chen et al 10 prospectively evaluated a group of 30 patients and found that PET/CT was superior to contrast-enhanced CT alone, with greater accuracy and specificity in assessing regional disease.…”
Section: Commentmentioning
confidence: 99%
“…Recent studies using PET/CT in the evaluation of treatment response in the neck have not routinely used SUV thresholds for deciding clinical response; instead, response was based on other factors such as focal uptake as visually determined with respect to the background activity that corresponded to a structural abnormality. 10-12,28,31 This is in contrast to the evaluation of PET imaging in the clinical staging of head and neck carcinomas, whereby SUV thresholds have been used to evaluate the likelihood of aggressive disease, response to therapy, and patient outcome. 32-34 Herein, we reported using cutoffs of SUV 2 and 2.5 in PET/CT performed on average 90.5 days after completion of treatment to evaluate treatment response in the neck, with a better NPV obtained with a PET/CT SUV threshold of 2.…”
Section: Commentmentioning
confidence: 99%